1985
DOI: 10.1177/0022002185016002004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Acculturation, Cognitive Style, and Intelligence

Abstract: The relationship of degree of Anglo-American acculturation to analytic cognitive style, nonverbal intelligence, and verbal intelligence was investigated using a cross-sectional development design. The results suggest that cognitive style does not play a particularly important role in an individual's performance on intelligence tests. In this study Mexican-Americans were no different from Anglos in nonverbal intellectual ability, but they performed less well on the vocabulary subtest. Overall this suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Given that statistical adjustments were made for age and education on test performance, and that GA participants were younger than Gn participants, and because there was no significant difference between GA and Gn reported years of education, this suggests that other factors mediated the cognitive performance of GA. Although studies comparing migrants to their peers from their country of origin are scarce, cognitive test performance differences have been noted Artiola i Fortuny et al, 1998;Berry et al, 1997;Boland, 2005;Gonzales & Roll, 1985;Lopez & Taussig, 1991;Manly, Miller et al, 1998;Touradji et al, 2001). Given the paucity of research and lack of relevant scientific data from which to draw from, the reasons for the current study findings are a matter for speculation.…”
Section: Cross-cultural Assessment Issuesmentioning
confidence: 81%
See 1 more Smart Citation
“…Given that statistical adjustments were made for age and education on test performance, and that GA participants were younger than Gn participants, and because there was no significant difference between GA and Gn reported years of education, this suggests that other factors mediated the cognitive performance of GA. Although studies comparing migrants to their peers from their country of origin are scarce, cognitive test performance differences have been noted Artiola i Fortuny et al, 1998;Berry et al, 1997;Boland, 2005;Gonzales & Roll, 1985;Lopez & Taussig, 1991;Manly, Miller et al, 1998;Touradji et al, 2001). Given the paucity of research and lack of relevant scientific data from which to draw from, the reasons for the current study findings are a matter for speculation.…”
Section: Cross-cultural Assessment Issuesmentioning
confidence: 81%
“…Such a comparison would illustrate whether test norms from a monolingual population are applicable to bilingual migrants. The limited cross-cultural literature, however, suggests that there are likely to be cognitive test performance differences due to factors such as country of residence, acculturation, and bilingual status (Artiola i Fortuny et al, 1998;Boland, 2005;Gonzales & Roll, 1985;Touradji, Manly, Jacobs, & Stern, 2001). Although GA and their peers from Greece have similar cultural values and beliefs, they are also likely to have cultural and linguistic differences.…”
Section: Rationale For the Present Studymentioning
confidence: 99%
“…Research generally suggests that acculturating to the dominant culture, or adapting certain dominant cultural traits, increases the likelihood of succeeding in school (Buenning & Tollefson; Gonzales & Roll, 1985). In addition, females seem to fit this model more so than do males (e.g., Vázquez, 1990).…”
Section: Acculturationmentioning
confidence: 99%
“…Many researchers found that white origin had better cognitive performances, especially involving verbal skills, when compared with persons of African, Hispanic, and Asian descent. However, when acculturation (i.e., age at which conversational English was first learned) was considered, they found no differences in cognitive skills across ethnic groups (Boone et al 2007;Fortuny et al 1998;Gonzales and Roll 1985;Razani et al 2007). In cognitive interviews, unacculturated research participants were reported to have more difficulties than the general public in performing cognitive skills.…”
Section: Factor To Affect Cognitive Performance: Age Education and mentioning
confidence: 97%